MAQASHID ASY-SYARIAH TINJAUAN FILSAFAT HUKUM ISLAM - Ahmad Sainul (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2020)
None of the laws of Allah SWT do not have a purpose for the benefit of the Ummah, but some people who leave the provisions of Allah SWT because they are considered not advanced in the community. So the focus of the problem in this paper is about what is the purpose of applying all the things that are ordered by Allah SWT. This issue will be seen by the writer from the perspective of Islamic legal philosophy with the method of literature through Islamic legal philosophy literature or other books relating to the topics discussed.The findings in this investigation unraveled clearly that all that were ordered by Allah SWT both Sunnah worship especially obligatory worship all had the purpose of Allah SWT starting from the prayer to prevent people from the heinous and unjust nature and so forth all the commands of Allah SWT oriented to the benefit of human beings human.